EMPLOYMENT ANALYSIS DISTRICT/CITY OF RIAU ISLANDS PROVINCE CITY EMPLOYMENT ANALYSIS DISTRICT/CITY PROVINCE OF RIAU ISLANDS - Simanjuntak, Jontro; Kurniawan, Putu Hari; Wibisono, Chablullah (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to explain the conditions of employment in the Riau Islands Province in 2014, which has decreased both the labor force and those who work and also increase the number of unemployed. The implementation of this research activity took place at the Regional Development Planning Agency (BAPPEDA) of the Riau Islands Province. The research method was done by observing secondary data with data from the Central Statistics Agency. This research is a descriptive study. Based on the results of the research, the highest number of the urban labor force is in Batam. The working-age group at the 15-44 years old have a more significant number than the age group above 45. Age groups by sex are more male workforce than the female workforce. Workforce education is more high school graduate education. Riau Islands has a workforce absorption of 896, 931 people with an unemployment rate of 69,160 people. The highest district/city labor force participation rate (TPAK) is the Anambas Island District. The highest occupation is the labor/employee employment field. Young male sex groups dominate the conclusions of the number of workforce and labor force participation. Batam is one of the most significant contributors to the workforce. The industry, trade, and hotel business sectors are the highest contributors to absorbing sports.